2000
DOI: 10.1080/713671113
|View full text |Cite
|
Sign up to set email alerts
|

Parents as Trainers About Disability in Low Income Countries

Abstract: A 5-day workshop is described which was designed speci cally to prepare parents to act as trainers for other parents with a child who has a disability. It also aimed to build their con dence and competence in training community groups as well as professional workers such as teachers. Data gathered at the end of the workshop con rmed that these aims were broadly met. Twelve months later, the participants had organised 19 training events throughout Lesotho for families and community groups and they were able to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…McConkey et al 35,110 The needs identified by parents were involvement of themselves as trainers for future service providers, increased awareness of rights of their children, better understanding by the community of their children's problems, and more specialists and community workers; primary outcome of the increased awareness in the community had been increased enrollment of children in schools, improved acceptance of the children in daily community activities and sports, identification of income-generating schemes for the affected, ensuring that an interpreter is available at the clinics to help the parents to communicate with the health staff, and increase in membership Mauritius…”
Section: Epidemiologymentioning
confidence: 99%
“…McConkey et al 35,110 The needs identified by parents were involvement of themselves as trainers for future service providers, increased awareness of rights of their children, better understanding by the community of their children's problems, and more specialists and community workers; primary outcome of the increased awareness in the community had been increased enrollment of children in schools, improved acceptance of the children in daily community activities and sports, identification of income-generating schemes for the affected, ensuring that an interpreter is available at the clinics to help the parents to communicate with the health staff, and increase in membership Mauritius…”
Section: Epidemiologymentioning
confidence: 99%
“…In Lesotho, one of Africa’s poorest countries, McConkey et al. (2000) conducted a 5‐day workshop for 21 parents of children with disabilities, including intellectual disabilities.…”
Section: Resultsmentioning
confidence: 99%
“… Community development It is clear that little advance in the welfare of children with developmental disabilities can occur unless there is an agreed goal to maximize potential of children with disabilities to participate in the general community, and an understanding that progress towards participation is achievable. The evidence, as demonstrated by McConkey et al. (2000), supports the value of, and we therefore recommend, parent‐led and government‐supported community activities to achieve a general motivation to assist children with disabilities. General child development The most extensively used and studied program to encourage the acquisition of independence skills and language development is the Portage Program (Cameron 1997).…”
Section: Recommendations and Conclusionmentioning
confidence: 94%
See 1 more Smart Citation
“…The sociocultural focus of programmatic intervention in response to the HIV and AIDS pandemic resonates with an earlier field of applied research and intervention on community‐based (re)habilitation (CBR) of children with disabilities (Nabuzoka, , ; Serpell, ). Several practitioners in Africa and other Majority World settings began in that period to explore ways of delivering education and developmental interventions to children with special needs in their homes (e.g., Marfo, ; Marfo, Walker, & Charles, ; McConkey, ; McConkey, Mariga, Braadland, & Mphole, ; Serpell, Mariga, & Harvey, ; Sturmey et al., ).…”
Section: Lessons Learnedmentioning
confidence: 99%